(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In the modern era of fast-moving world, lies the under rated plethora of so many infections and disorders which might seem so common yet with numerous complications and poorer outcomes. One such common disease which is prevailing in children is the acute rheumatic fever. With the word rheumatic, it is alarming itself because Rheumatology as such is a new Science which has a lot of research going on and so many areas which are touched upon less. The major setback lies upon the prognostic factors of the disease as such.